AKADEMIK LITSEY O'QUVCHILARIDA FUQAROLIK POZITSIYANI TARBIYALASHNING NAZARIY ASOSLARI - Orinbetov, N.T. (SCIENCE and SOCIETY, 2022)
The article presents the concepts of citizenship, citizenship, active citizenship, position, social activity and their meaning. The article also outlines the scientific and theoretical foundations of educating students of academic lyceums to understand civic, active civic, social activity and civic position in the process of education and upbringing.
Keywords: citizen; citizenship; civil society; civic stand; the rule of law; rights and freedoms; values